Experiences of nurses working in a rural primary health-care setting in Mopani district, Limpopo Province - MP Mohale (Curationis, 2008)
Professional nurses working in rural, primary health-care settings are experiencing burnout due to serious shortages of personnel. This is exacerbated by the brain drain of nurses leaving the country. Rural settings are resource constrained in terms of personnel and equipment. This results in dissatisfaction among nurses due to the unbearable working conditions which result in stress and frustration. A qualitative, explorative, descriptive study was conducted to explore and describe the experiences of nurses working in a rural primary health-care setting in the greater Letaba sub district in Limpopo Province. Purposive sampling was used to identify the participants. Data was collected in the form of in-depth interviews. The study revealed that nurses working in primary health-care settings were experiencing emotional and physical strain as a result of the shortage of human resources. It was recommended that policies that meet the health-care needs of rural communities be developed, and that strategies to retain professional nurses in primary health-care settings be formulated.